2020
DOI: 10.1186/s12893-020-00775-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of laparoscopy on mast cell degranulation and mesothelium thickness in rats

Abstract: Background: Laparoscopy induces adhesion due to ischemia-reperfusion injury. However, the detail pathomechanism is poorly understood. This study aimed to investigate the impact of laparoscopy on mast cell and mesothelium morphological changes in the rat. Methods: Forty-nine males of Sprague-Dawley Rattus norvegicus were divided into four groups: a) control and b) intervention groups P1, P2, and P3 that underwent 60 min laparoscopic using carbon dioxide (CO 2) insufflation at 8, 10, and 12 mmHg groups, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…The control group (n = 6) did not receive pneumoperitoneum. The intervention groups of P-5 mmHg, P-8 mmHg, P-10 mmHg, and P-12 mmHg (all n = 6) were given 5, 8, 10, and 12 mmHg CO 2 pneumoperitoneum, respectively [ 6 , 12 ]. Our study strictly followed the ethical and euthanasia guidelines for animal research ( http://risetcenterfk.ulm.ac.id/euthanasia/ ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The control group (n = 6) did not receive pneumoperitoneum. The intervention groups of P-5 mmHg, P-8 mmHg, P-10 mmHg, and P-12 mmHg (all n = 6) were given 5, 8, 10, and 12 mmHg CO 2 pneumoperitoneum, respectively [ 6 , 12 ]. Our study strictly followed the ethical and euthanasia guidelines for animal research ( http://risetcenterfk.ulm.ac.id/euthanasia/ ).…”
Section: Methodsmentioning
confidence: 99%
“…According to the previous study [ 6 ], 60-min laparoscopy was performed in a sterile area after shaving and povidone-iodine application. Ten mg/kg BW intramuscular injections of ketamine hydrochloride (KTM-10; PT Guardian Pharmatama, No.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, similar findings were observed by Poerwosusanta et al in rats exposed to 8, 10, and 12 mmHg pneumoperitoneum. e authors found a progressive and significant increase in mastcell peritoneal infiltration and degranulation with an increase in pressure 7 days after surgery [29]. Paralleling with local acute response, gas pressure was described as a factor influencing systemic inflammation.…”
Section: Inflammationmentioning
confidence: 96%
“…Poerwosusanta et al investigated the role of mast cell degranulation in mesothelial injury. Mesothelial injury was carried out by performing laparoscopic surgeries in rats at different intra-abdominal inflation pressures (74). They showed that an increased intraabdominal pressure-and presumably increased stress to the mesothelium-led to an increased number of mast cells that infiltrated the mesothelium.…”
Section: Dendritic Cells and Mast Cellsmentioning
confidence: 99%